Laurentaeglyphea Forest, 2006 (Crustacea, Decapoda, Glypheidae): a cautionary tale of nomina nuda and the unpredictability of publication schedules - Boyko, Christopher B. (Zootaxa, 2008)
Glypheid crustaceans have been the source of much recent discussion, particularly in a phylogenetic context (Schram & Ahyong, 2002; Dixon et al., 2003; Ahyong & O’Meally, 2004), an interest initiated by the discovery and report of a living example of this long-thought extinct group by Forest & de Saint Laurent (1975). Subsequent collections resulted in additional information about the biology, ecology, morphology, and biogeography of this “unique” living glypheid species, Neoglyphea inopinata Forest & de Saint Laurent, 1975 (Forest & de Saint Laurent, 1976; 1981; 1989; Bruce, 1988).